IMPLEMENTATION OF "EVALUATION-VALUE ADDED INTELLECTUAL COEFFICIENT” (EV-VAIC) AS EXPANSION OF INTELLECTUAL CAPITAL MEASUREMENT MODEL - Santy Mayda, Batubara; Salawati, Sahari; Mohammad, Jais (Allied Business Academies, 2021)
The study aims to explain and describe the implementation of Ev-VAIC as the expansion of the Intellectual Capital measurement model, whether the Ev-VAIC model's feasible as the new measurement Intellectual Capital (IC) model. There are four components, namely physical capital, financial capital, human capital and structural capital. This study will demonstrate and develop a case study. The company has listed the Indonesian Stock Exchange to assess the Ev-VAIC model's feasibility as the new measurement Intellectual Capital (IC) model. The results of each Intellectual Capital (IC) component evaluation were summarized in a new sheet to count the score total and footprint (graphical representation) of each Intellectual Capital (IC) component. The use of EvVAIC model could find out which components are good and are not good, which must be improved to support the business performance. So, the Ev-VAIC results could be used as parameters for decision-makers to evaluate how the company manages the Intellectual capital to maximize the value the company.